Penerapan Metode Certainty Factor Dalam Mendiagnosa Penyakit Skizofrenia berbasis Komputer - Cynthia Silaban (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Current technological developments are very rapid, so the development of these technologies is very beneficial in all fields including health. In today's case there are a lot of things that are detrimental to others even yourself. Where the case can occur self-harm to the loss of level of awareness in controlling emotions. The purpose of this study is to diagnose schizophrenia and provide solutions to the conditions experienced through the application of an expert system. Certainty Factor method can provide ease in making diagnoses and provide more accurate diagnoses based on previous events and can be revised again in solving new problems